ANALYSIS OF THE VARIATION OF VIBRATIONS THAT APPEAR DURING TURNING WORKS WITH TRANSVERSE FEED DUE TO THE MODIFICATION OF THE FUNCTIONAL GEOMETRY OF THE CUTTING TOOL - Mădălin TOMESCU; Ionela Magdalena ROTARU (Fiabilitate şi Durabilitate, 2023)
The paper aims to analyze the way in which the variation of the vibrations that appear during the machining processes by chipping during the transverse turning operation evolves due to the variation of the functional geometry of the chipping tool. The turning technological process with transverse feed is carried out with a variable cutting speed, and this determines a variation of the functional geometry of the tool. Thus, in the work, the optimal constructive geometry of a lathe knife that can be used for turning a piece with a diameter was established 150mm and the vibrations during processing by turning with transverse feed of C45 steel (1.0503): EN 10277-2- 2008- 150mm . Under these conditions, a correlation was identified between the values of the functional geometric parameters of the knife used for transverse turning and the vibrations measured during processing.